Euripides and the poetics of sorrow : art, gender, and commemoration in Alcestis, Hippolytus, and Hecuba - Segal, Charles, 1936-2002 (e-Duke books scholarly collection., 1993)
Where is the pleasure in tragedy? This question, how suffering and sorrow become the stuff of aesthetic delight, is at the center of Charles Segal's new book, which collects and expands his recent explorations of Euripides' art. Alcestis, Hippolytus, and Hecuba, the three early plays interpreted here, are linked by common themes of violence, death, lamentation and mourning, and by their implicit definitions of male and female roles. Segal shows how these plays draw on ancient traditions of poetic and ritual commemoration, particularly epic song, and at the same time refashion these traditions.